2019
DOI: 10.1371/journal.pone.0215648
|View full text |Cite
|
Sign up to set email alerts
|

Three novel compound heterozygous IL12RB1 mutations in Chinese patients with Mendelian susceptibility to mycobacterial disease

Abstract: Mendelian Susceptibility to Mycobacterial Diseases (MSMD) is a primary immunodeficiency disease (PID) characterized by variable susceptibility to weakly virulent mycobacteria ( Bacille Calmette-Guerin , BCG ) and various intramacrophagic bacteria, fungi, parasites. Mycobacterial disease generally begins in childhood, more rarely during adolescence and adulthood. The pathogenesis of MSMD is the inherited impaired production of interferon gamma (IFN-γ) or inadequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…1 ). All variants have been previously reported [ 21 , 22 ] except for c.1750C > T, a missense variant that is exceedingly rare (gnomAD exomes AF 0.000004, allele count one Latino individual) and likely pathogenic, with a CADD Phred score of 23.4 (minimum significance cutoff value for IL12RB1 at 95% CI 3.65) [ 23 ], classified as Pathogenic in ClinVar, and as VUS by ACMG criteria ( http://varsome.com .) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). All variants have been previously reported [ 21 , 22 ] except for c.1750C > T, a missense variant that is exceedingly rare (gnomAD exomes AF 0.000004, allele count one Latino individual) and likely pathogenic, with a CADD Phred score of 23.4 (minimum significance cutoff value for IL12RB1 at 95% CI 3.65) [ 23 ], classified as Pathogenic in ClinVar, and as VUS by ACMG criteria ( http://varsome.com .) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Globally, a wide range of clinical manifestations of MSMD, from transient localized to persistent disseminated infections with impaired granuloma formation, has been reported, and Salmonella infections occurred in about half the reported patients (43). In China, 65 patients with MSMD in 20 publications (35,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) were described, along with 9 gene mutations (IFNGR1, IFNGR2, ISG15, IL12B, IL12RB1, STAT1, TYK2, NEMO, CYBB) were noted. IL-12RB1 deficiency was the most common molecular defect, accounting for 52% of all cases, followed by IFNGR1 (22%) and STAT1 (9%) (Figure 2).…”
Section: Genetic Profiles and Clinical Manifestations Of Reported Msm...mentioning
confidence: 99%
“…The other 35 Chinese cases were reported in 19 publications from Mainland China, Hongkong, and Taiwan (35,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Of them, 19 (54.3%) were female and 16 (45.7%) were male; the medium age at onset was 4 months.…”
Section: Genetic Profiles and Clinical Manifestations Of Reported Msm...mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-12Rβ1 is responsible for the formation of IL-12 and IL-23 receptors. It has been reported that IFN-γ production is low and there is no IL-12 response (T and NK cells) in patients with IL-12Rβ1 deficiency (6,7).…”
Section: Introductionmentioning
confidence: 99%